Calvarial tuberculosis of the parietal bone: A rare complication after dental extraction - Nair, Anup; Mehrotra, Anant; Das, Kuntal; Kumar, Brijesh; Srivastav, Arun; Sahu, Rabi; Kumar, Raj (Asian Journal of Neurosurgery, 2015)
Tuberculosis (TB) is a well-known endemic in developing countries. However calvarial TB is quiet rare even in such endemic areas. The most common sites affected are the frontal and parietal bones with destruction of both the inner and outer table. We hereby report a young male presenting to us with scalp swelling in the right temporal region with pus discharging sinus after an episode of tooth extraction for dental infection. Radiology revealed a loculated swelling within the right temporalis muscle and an associated bony defect in the right parietal bone. The patient was operated upon and the biopsy was suggestive of tubercular pathology. The patient improved on antitubercular therapy. The rare presentation of calvarial TB occurring secondary to dental infection along with relevant literature is discussed here.
Keywords: Calvarial; hematogenous; pulmonary; tuberculosis